Exploration of Jejamok Games as Local Wisdom: Basis for Developing E-Comics for Integer Learning - Ratih Handayani; Ratu Ilma Indra Putri; Zulkardi; Darmawijoyo (Riemann: Research of Mathematics and Mathematics Education, 2026)
The persistent challenges students face in understanding integers indicate the need for learning approaches that connect abstract mathematical concepts with meaningful real-life experiences. Although culturally grounded contexts have been widely recommended in mathematics education, there remains a limited understanding of how specific traditional games can be systematically interpreted to reveal their embedded mathematical structures and support conceptual learning. This study seeks to investigate the Jejamok traditional game from North Lampung through an ethnomathematics perspective to identify its potential as a context for learning integer concepts and as a basis for developing instructional media. A qualitative exploratory approach was employed, involving literature review, field observations, and interviews with local community members and teachers. The findings reveal that Jejamok embodies several key mathematical ideas related to integers, including (1) positive and negative values represented through capture and release actions, (2) addition and subtraction of integers through score changes, and (3) comparison of quantities and strategic decision-making based on game situations. These concepts emerge naturally from the game’s scoring system and player interactions, providing a meaningful bridge between informal experiences and formal mathematical understanding. Furthermore, the game structure reflects a form of situated mathematical representation that supports progressive mathematization within the PMRI framework. In addition, Jejamok reflects important cultural values such as cooperation, sportsmanship, and nengah nyappur, which contribute to social learning. These findings suggest that Jejamok can serve not only as a contextual learning resource but also as a conceptual foundation for developing culturally responsive instructional media, such as e-comics. This study contributes to the development of culturally grounded mathematics instruction by offering an empirically supported and theoretically informed model for connecting local cultural practices with formal mathematical learning.